Calcium silicate based cements: key factor in the success of direct pulp capping. Literature review. - Granados-Laura, Shirley (2022)
Traditionally, calcium hydroxide (HC) was considered the material of choice for direct pulp capping (RPD); but this has changed over the years due to the various disadvantages it presents. Calcium silicate-based cements (CSC) have properties that are advantageous to HC such as: bioactivity, biocompatibility, shorter setting time, sealing capacity and resistance, which they are used in a variety of endodontic procedures, including RPD.This review article compiles information from the manual search of original scientific research articles and literature reviews of the Medline / PubMed database. The varieties of CSC, their mechanism of action, disadvantages, related factors and rates of clinical success in their application in cases of RPD are described.